A Web Screening on Educational Initiatives to Increase Citizens’ Literacy on Genomics and Genetics - Sassano, Michele; Calabrò, Giovanna Elisa; Boccia, Stefania (Frontiers in Genetics, 2021)
Introduction. Population awareness and empowerment in omics science represents a fundamental driver to increase the adoption of evidence-based approaches in personalized medicine. In this context a pivotal role is played by citizens' literacy, and educational initiatives carried out in this context are key assets to drive future effective interventions. With the present study we summarized the educational initiatives conducted worldwide aimed at increasing citizens’ literacy in omics sciences. Materials and methods. We conducted a web search of educational initiatives aimed at improving citizens’ literacy on omics sciences undertaken worldwide, by using three search engines (Google, Bing, and Yahoo Search), in English and in Italian languages. Results. We identified five initiatives in Europe, 22 in non-European countries, and 13 in Italy. Overall, the majority (69%) were web-based initiatives while 31% required in-person attendance. The online initiatives included web-pages for reading, online lessons/courses, web portals, videos/short movies, animations, and apps for mobile devices. The residential initiatives, instead, included exhibitions, seminars, courses, symposia, information stands in public places, guided visits at research laboratories, and interactive laboratories. All the initiatives were highly heterogeneous in terms of methodologies and topics addressed. Discussion and conclusion. Overall, we identified a variety of initiatives aimed at improving citizens’ literacy on omics sciences, with the largest majority carried out in United States and being web-based. Our results showed heterogeneity among initiatives as to dealt topics and adopted methods. Further research is needed, however, to quantitatively assess the effectiveness of educational initiatives to improve citizens’ literacy on omics sciences.